Perancangan Sistem Manajemen Toko berbasis Web (Studi Kasus pada Toko Mebel Sampoerna) - Prama Pradipta Adiwignya; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Sampoerna Furniture is one of the shops that engaged in the furniture sector that located in Probolinggo which provides various kinds of furniture products. This store still uses traditional management methods for all of their business processes. This causes the range of stores to be limited only in that city. Sales record are still done manually in the book. The problem is the data record is not neat which can cause problems on data recap and can also make it difficult for the owner to get accurate sales reports. Then there is also the problem of documentation on stock items. Because to solve this problem the researchers built a store management system with the waterfall development method and used the ReactJs, NodeJs and MySQL as programming languages. The process of elicitation and analysis has been carried out and resulted in 2 actors with 20 functional and 1 non-functional. Validation testing also used in this study to test the results of the suitability of the implementation with the design.